Penerapan Kahoot! dan Poster Digital sebagai Media Evaluasi Penguasaan Kosakata Baku dalam Upaya Pembinaan Bahasa Indonesia di Media Sosial - Galih Ahmad Rivaldi; Syifa Nurlatifah; Lisa Herlina; Yuni Ertinawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study was motivated by the reality that people do not fully understand the proper use of Indonesian, especially in terms of standard vocabulary, terminology, and synonyms. Therefore, the purpose of this study was to promote Indonesian language skills through educational content in the form of digital posters on Instagram in order to reach a wider audience. In addition, the author also used the Kahoot! application as an evaluation tool to measure social media users' understanding of standard vocabulary. The method used in this study was a qualitative method with a descriptive approach. The subjects of this study were the general public who are active users of social media, especially on the Instagram platform, and there were 34 respondents. The object of this study was the respondents' answers to the quiz on the Kahoot! application. The results of this study concluded that there is still a low level of enthusiasm among the public, especially students, in using Indonesian. However, this can be minimized through the use of social media, such as the creation of interesting educational content in the form of digital posters, which have proven to be effective as an effort to foster Indonesian language in the era of digitalization.